Cu and Co nanoparticles co-doped MIL-101 as a novel adsorbent for efficient removal of tetracycline from aqueous solutions - Jin, Jiahui; Yang, Zhaohui; Xiong, Weiping; Zhou, Yaoyu; Xu, Rui; Zhang, Yanru; Cao, Jiao; Li, Xin; Zhou, Chengyun (The Science of the total environment, 2019)
Chromium metal-organic framework (MIL-101(Cr)) has been widely studied for removing organic contaminants from aqueous solutions due to its excellent water stability and giant pore size, but its low adsorption capacity limits the application. In this study, a new adsorbent MIL-101 loaded with CuCo bimetallic nanoparticles (CuCo/MIL-101) was successfully fabricated and applied in removal of tetracycline (TC) from aqueous solutions. The adsorption capacity of CuCo/MIL-101 for TC increased by 140% compared with that of pure MIL-101, which may be attributed to the chemical bonding between Cu and Co BNPs in MIL-101 and TC molecules. The effects of pH, ionic strength, humic acid and contact time on the adsorption were also discussed in detail. The results showed that the removal efficiency of TC solution with high concentration (100 mg L−1) by CuCo/MIL-101 was still as high as 82.9%. The data of adsorption kinetics and isotherms could be well fitted by Elovich model and Freundlich model, respectively. According to the fitting parameters, the maximum adsorption capacity of CuCo/MIL-101 reached up to 225.179 mg g−1. Additionally, the adsorption process of TC onto CuCo/MIL-101 was spontaneous and endothermic. Electrostatic interactions could play an important role in the adsorption process. The enhanced adsorption capacity, excellent reusability and water stability demonstrated the potential of CuCo/MIL-101 composite as a novel adsorbent for the removal of TC from aqueous solutions. [Display omitted] •MIL-101 doped with Cu and Co bimetallic nanoparticles was utilized as an adsorbent to remove tetracycline for the first time.•The synergistic effect between Cu and Co made the adsorption capacity of CuCo/MIL-101 significantly enhanced.•Electrostatic interaction played an important role in the adsorption process.•The good reusability and stability of CuCo/MIL-101 proved its potential to remove tetracycline from actual wastewater.